An Alternate Technique of Applying Lag Screw for Fixation of Distal Fibula Fracture: Posterior to Anterior Interfragmentary Compression Screw. Issue 6 (December 2017) - Vijimohan, Suganth Jayaraman; Haque, Syed; Ellis, David
Ankle fractures are one of the most common lower limb fractures, representing a significant portion of the trauma workload. Marked proportion of these is isolated intraarticular lateral malleolus fractures. Anatomical reduction and rigid internal fixation using lag screw (interfragmentary screw) to provide interfragmentary compression has remained the choice of treatment in selected lateral malleolus fractures. Applying interfragmentary compression screw from anterior to the posterior surface of the fibula has been the traditional method of performing this. In this article, we describe an alternate method of applying posterior-anterior interfragmentary compression screw to the fibula fractures. We will also discuss the benefits it provides such as minimizing the chances of hardware-related peroneal tendon irritation. Further argument will focus on the mechanical benefit this will render while providing equal clinical outcome of the time tested anterior-posterior interfragmentary compression screw. Levels of Evidence: Level V: Therapeutic comparison